Economic effects in the UK periphery from unconventional gas development: Evidence from Wales. (1st January 2019) - Evans, Neil; Jones, Calvin; Munday, Max; Song, Meng
Abstract: The paper examines the potential regional economic benefits of the development of unconventional gas. Wales (UK) represents an interesting lens through which to examine the expected effects of unconventional gas developments. In spite of significant resource endowments the region has found it difficult to internalise the economic benefits from prior energy developments. We examine whether possible commercial exploitation of unconventional gas in Wales will be any different from recent rounds of resource and energy investment. We address the challenges for resource peripheries in embedding economic activity linked to unconventional gas and show that there are dangers in generalising economic impact evidence from other states. Highlights: Unconventional gas development in Wales may have limited regional economic benefit. Region shown to have difficulty internalising economic benefits. Supply side constraints in local economy critical. Scenario analysis reveals limited employment benefits from any sector growth.